Electrical properties of strained germanium nanofilm - Luniov, S.V.; Nazarchuk , P.F.; Burban, O.V. (Physics and Chemistry of Solid State, 2021)
Dependences of the concentration of intrinsic current carriers, electron and hole mobilities and specific conductivity for strained germanium nanofilms grown on the Si, Ge(0,64)Si(0,36) and Ge(0,9)Si(0,1) substrates with crystallographic orientation (001), on their thickness at different temperatures were calculated on the basis of the statistics of non-degenerate two-dimensional electron and hole gas in semiconductors. The electrical properties of such nanofilms are determined by the peculiarities of their band structure. It is established that the effects of dimensional quantization, the probability of which increases with decreasing temperature, become significant for germanium nanofilms with the thickness of d<7 nm. The presence of such effects explains the significant increase in the specific conductivity and the decrease in the intrinsic concentration of current carriers for these nanofilms. The electron and hole mobility in the investigated germanium nanofilms is lower in relation to such unstrained nanofilms. Only for the strained germanium nanofilm with the thickness of d> 50 nm grown on the Ge(0,9)Si(0,1) substrate, an increase in the hole mobility at room temperature of more than 1.5 times was obtained. The obtained results of the electrical properties of strained germanium nanofilms can be used in producing on their basis new elements of nanoelectronic.